1999
DOI: 10.1152/ajpheart.1999.276.1.h141
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of β-adrenergic responsiveness of L-type Ca2+ current by IL-1β in rat ventricular myocytes

Abstract: The possible mechanism by which interleukin-1β (IL-1β) affects β-adrenergic responsiveness of L-type Ca2+ current ( I Ca,L) was examined in adult rat ventricular myocytes by use of whole cell patch-clamp techniques. In the presence of isoproterenol (Iso), exposure for 3 min to IL-1β suppressed the Iso-activated I Ca,L. In the presence of IL-1β, the response of I Ca,L to Iso was decreased, and the EC50 for Iso stimulation was increased. However, IL-1β had no effect on [3H]CGP-12177 binding, displacement of [3H]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
1
36
0
2
Order By: Relevance
“…Recent studies have highlighted the involvement of IL-1 signaling in heart disease (13). IL-1 has been shown to induce impairment in β-adrenergic responsiveness and contractility, both in vitro and in vivo (16,32). Single or repeated injections of recombinant murine IL-1β induce systolic dysfunction and impaired contractile reserve in absence of structural changes (16,33).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the involvement of IL-1 signaling in heart disease (13). IL-1 has been shown to induce impairment in β-adrenergic responsiveness and contractility, both in vitro and in vivo (16,32). Single or repeated injections of recombinant murine IL-1β induce systolic dysfunction and impaired contractile reserve in absence of structural changes (16,33).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In general, in vitro introduction of inflammatory mediators (e.g., interleukines, tumor necrosis factor-a and interferon-a) has resulted in reduced responsiveness, affinitym and/or density of b-adrenergic receptors. [25][26][27][28][29] These in vitro observations may also be attributed to an overexpression of NO secondary to inflammation or introduction of other pro-inflammatory mediators. 30 Our AA rats showed almost threefold greater nitrate concentration than controls.…”
Section: Discussionmentioning
confidence: 99%
“…In isolated mammalian myocytes, within minutes of exposure to cytokines such as TNF-␣, IL-1␤, and IL-6, there is an inhibition of catecholamine-stimulated contractility, 71,75 cAMP generation, 71 and I Ca augmentation. 75,76 The mechanism for this defect in ␤-AR signal transduction is not clear, although one study 76 suggested a mechanism unrelated to alterations in ␤-AR binding, adenylyl cyclase (AC) activity, or cAMP. Finally, in another isolated myocyte study, IL-2 was shown to reduce cell contraction and Ca 2ϩ transients via the cardiac opioid receptor, a mechanism dependent on pertussis toxinsensitive G protein and phospholipase C. 62 Further studies are needed to determine the mechanistic role of these signal transduction pathways.…”
Section: Other Mechanismsmentioning
confidence: 99%